2020
DOI: 10.1038/s41598-020-60035-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in bacterial isolates from freshwater samples in Fildes Peninsula, King George Island, Antarctica

Abstract: Anthropic activity in Antarctica has been increasing considerably in recent years, which could have an important impact on the local microbiota affecting multiple features, including the bacterial resistome. As such, our study focused on determining the antibiotic-resistance patterns and antibioticresistance genes of bacteria recovered from freshwater samples collected in areas of Antarctica under different degrees of human influence. Aerobic heterotrophic bacteria were subjected to antibiotic susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 51 publications
5
39
1
2
Order By: Relevance
“…The microorganisms isolated from the eyes of a Gentoo penguin chick in the present study differ from those reported to have been isolated from the eyes of mammals and exotic birds in previous studies ( Silvanose et al 2001;Cullen, 2003;Bonelli et al 2014;Cakir et al 2014;Sala et al 2016). Furthermore, the microorganisms isolated in the present study have been determined to differ from the bacteria reported to have been detected in freshwater samples from the same location (Jara et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…The microorganisms isolated from the eyes of a Gentoo penguin chick in the present study differ from those reported to have been isolated from the eyes of mammals and exotic birds in previous studies ( Silvanose et al 2001;Cullen, 2003;Bonelli et al 2014;Cakir et al 2014;Sala et al 2016). Furthermore, the microorganisms isolated in the present study have been determined to differ from the bacteria reported to have been detected in freshwater samples from the same location (Jara et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…There was a notable presence of sul1 , which expresses resistance to synthetic or semi-synthetic antibiotics such as sulphonamides. A recent study detected resistance against these antibiotics in bacteria recovered from freshwater samples collected close to Antarctic research stations [ 39 ], which was attributed to poor waste water treatment. Nevertheless, sul1 is not necessarily an indicator of human activity, as it is usually present in environmental bacteria from soils and waters, even in the Antarctic [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both the bio-essentiality and abuse of metals, as well as antibiotics, can led to bacterial resistance phenomena. These latter are ubiquitous and have been also detected in bacteria from Antarctic seawater, marine sediment and benthic organisms, as well as freshwater environments and soils [ 85 , 86 , 87 ]. Tolerance towards heavy metals (resulting particularly evident in isolates from TF brines) was higher for nickel and copper than for mercury and cobalt, thus appearing strictly related to the determined metal concentrations.…”
Section: Discussionmentioning
confidence: 99%